Identification of QTL for adult plant resistance to stripe rust in bread wheat line C33 - Jiang-tao LUO; Jian-min ZHENG; Hong-shen WAN; Wu-yun YANG; Shi-zhao LI; Zong-jun PU (Journal of Integrative Agriculture, 2020)
Stripe rust, caused by Puccinia striiformis f. sp. tritici, is a serious disease in bread wheat (Triticum aestivum L.). Identification and use of adult plant resistance (APR) resources are important for stripe rust resistance breeding. Bread wheat line C33 is an exotic germplasm that has shown stable APR to stripe rust for more than 10 years in Sichuan Province of China. Here, 183 recombinant inbred lines (RILs) derived from the cross between C33 and a susceptible line X440 were genotyped with diversity arrays technology (DArT) markers to identify resistance quantitative trait locus (QTL). Field trials were conducted in five years at Chengdu and Xindu of Sichuan Province, using maximum disease severity (MDS) as stripe rust reaction phenotypes. A total of four quantitative trait loci (QTLs) were detected, respectively designed as QYr.saas-3AS, QYr.saas-5AL, QYr.saas-5BL, and QYr.saas-7DS, explaining 4.14–15.21% of the phenotypic variances. QYr.saas-5BL and QYr.saas-7DS were contributed by C33. However, the level for stripe rust resistance contributed by them was not strong as C33, suggesting the presence of other unidentified QTLs in C33. QYr.saas-7DS corresponded to Yr18 and QYr.saas-5BL remains to be formally named. The RIL lines carrying combinations QYr.saas-5AL, QYr.saas-5BL, and QYr.saas-7DS showed comparability resistance with C33. The present study provides resources to pyramid diverse genes into locally adapted elite germplasm to improve the stripe rust resistance of bread wheat.